2015
DOI: 10.1177/0018726715602046
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations between employees’ beliefs about the quality of the change management process, affective commitment to change and psychological empowerment

Abstract: Organizational changes are costly ventures that too often fail to deliver the expected outcomes. Psychological empowerment (PE) and affective commitment to change (ACC) are proposed as especially important in turbulent contexts characterized by multiple and ongoing changes requiring employees' continuing contributions. In such a context, employees' beliefs that the changes are necessary, legitimate, and will be supported, are presumed to increase PE and ACC. In a three-wave longitudinal panel study of 819 empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(122 citation statements)
references
References 77 publications
(212 reference statements)
3
117
0
2
Order By: Relevance
“…Through participative decision-making of empowering leadership [45], employees gain a sense of control over their performance and feel psychological empowerment [19], which can increase organizational commitment [33,46]. Psychological empowerment is an important factor in organizational change, as it allows employees to have control over their work and influence the process of organizational change [33,47]. Psychologically empowered employees are encouraged by organization leaders to engage in the process of organizational change.…”
Section: Empowering Leadership and Commitment To Organizational Changementioning
confidence: 99%
“…Through participative decision-making of empowering leadership [45], employees gain a sense of control over their performance and feel psychological empowerment [19], which can increase organizational commitment [33,46]. Psychological empowerment is an important factor in organizational change, as it allows employees to have control over their work and influence the process of organizational change [33,47]. Psychologically empowered employees are encouraged by organization leaders to engage in the process of organizational change.…”
Section: Empowering Leadership and Commitment To Organizational Changementioning
confidence: 99%
“…Significant as such contributions are, scholars operationalising these models have tended to downplay or ignore employment relations institutions and the collective dimension to the employment relationship in their analytical designs and theorisations, even though the measurement scales do not specifically exclude such an approach. For example, the belief that change has value for employees is a central feature of affective commitment to change (Herscovitch and Meyer cited in Morin et al, , p. 842). Similarly, a predictor of “prochange behaviour” is the extent to which individuals feel they are treated fairly and justly by their organisation (Rodell and Colquitt cited in Fuchs & Edwards, , p. 41).…”
Section: Organisational Change Workplace Partnership and Distributementioning
confidence: 99%
“…Hypothesis 5 hypothesizes the influence of change favorableness on affective commitment to change and exit-based withdrawal, and, along this pathway, the role of trust also attenuates the influence of change favorableness on organizational identification. In this regard, Morin et al [66] argue that the impact of factors including favorableness, trust in management, and justice in a change context, remain less researched. Along these lines, Stinglhamber et al [32] found that favorable work experiences increase employee affective commitment to organizations mediated by organizational identification.…”
Section: The Moderating Effect Of Trustmentioning
confidence: 99%